A Proposal of a Universal Remote Control System Based on Head Movements - Batista, Cassio T. Batista; Campos, Erick M. Campos; Neto, Nelson C. Sampaio Neto (Teste, 2018)
Technological developments converge to make people interact with electronic devices in an easy way. For people with disabilities, however, that interaction becomes something more than simple: it becomes possible. The current work presents a proposal of an open-source, low cost universal remote control system that translates user's head poses into commands to electronic devices. In addition, a proximity sensor circuit was combined to radio-frequency modules in order to act as a wireless switch. Among the applications found with respect to alternative remote controls, none of them supports head gestures as input, which would certainly make them a viable option to people whose upper limbs are compromised. A mean opinion score questionnaire was applied to volunteers in order to evaluate the system. The results show great interest of the users in this kind of technology.